Students Perceptions of Cigarette, Graphic Health Warnings, Fast Food, and Gadget Use on Physical Activity (Evidence Based for Health Promoting University Program Recommendations) - Yoga Putra Wibowo; Regista Tri Puspitasari; Arneta Meihua Inaya; Vina Yulia Anhar; Ihya Hazairin Noor; Dominicha Ernalem Tarigan (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2023)
Based on BPS data, consumption of cigarettes and e-cigarettes by teenagers over 15 years old decreased by 2.62% from the previous year, but it still has the potential to be dangerous. Adolescent health is quite worrying considering that teenagers are the main figures who can carry forward the vision for the future. The aim of this research is to obtain empirical evidence and appropriate strategies for implementing the HPU program. The method used is quantitative, through a survey with Franken-wallen incidental sampling, respondents are students pursuing higher education in 3 districts/cities, namely Banjar Regency, Banjarmasin City and Banjarbaru City. The survey was conducted from September to October (2 weeks) online. The results of this study show that cigarette and e-cigarette consumption is quite low, but respondents' perceptions regarding are still comprehensive (71%), including regarding graphic health warnings on cigarette packaging (80.1%). Interest in consuming fast food tends to be high (64.2%), who regularly consume fruit and vegetables (37.5% and 33.5%). The use of gadgets among students is very high (58%) and complaints regarding CVS also appear (45.5%). To support HPU, a specific action plan is needed, especially to strengthen understanding of the impact of consumption of cigarettes and so on.